In vitro and in silico investigations of the pro-apoptotic activity of Opuntia ficus-indica cladode extracts against K562 cells - Oncul, Sule; Becer, Eda; Mega Tiber, Pinar; Terali, Kerem; Aykac, Asli (Walter de Gruyter Gmbh, 2024)
Objectives: Cladodes of Opuntia ficus-indica (OFI) are thought to be an excellent source of bioactive compounds, making them an aspirant for the manufacture of health-promoting compounds. This study aims at exploring the pro-apoptotic effects of spiny and thornless OFI cladode extracts on the human immortalized myelogenous leukemia cell line (K562). Methods: The ethanol extraction method was used for preparing cladode extract. Cytotoxicity was evaluated by MTT assays. Membrane permeability/damage was detected by annexin V-binding assays, and mitochondrial damage/alteration was detected by mitochondrial membrane potential measurements. The protein expression quantities of Bax and Bcl-2 were assessed by Western blotting. The pro-apoptotic potentials of the main spiny and thornless OFI extract constituents were investigated structurally and mechanistically using protein-ligand docking and interaction profiling. Results: Spiny OFI extract displayed a stronger cytotoxic effect than thornless OFI extract on K562 cells. In silico findings agreed with the pro-apoptotic action observed in vitro. Conclusions: Finally, our findings imply that OFI extracts cause apoptosis in K562 cells in order to have anti-cancer effects.
Keywords: Opuntia ficus-indica; cancer; extract; apoptosis; in silico